Augmented-feedback training improves cognitive motor performance of soccer players - Hicheur, H.; Chauvin, A.; Cavin, V.; Fuchslocher, J.; Tschopp, M.; Taube, W. (Medicine & Science in Sports & Exercise, 2020)
Purpose: In this study, we tested the hypothesis that augmented feedback (AF) training can improve both perceptual-cognitive and/or motor skills specific to soccer. Methods: Three groups of young elite players (U14-U15 categories) performed a test consisting in passing the ball as accurately and as quickly as possible toward a visual target moving briefly across a large screen located at 6 m from the player. The performed task required players to correctly perceive the target, anticipate its future location, and to adequately adjust the pass direction and power. The control group (CON) performed normal soccer training and was compared with two visuomotor training groups (AF and no-feedback [NF]) that followed the same training regime but integrated series of 32 passes three times per week over a 17-d period into their normal soccer training. Objective measurements of the passing performance were provided using a high-technology system (COGNIFOOT) before, during, and after training. During training, only players of the AF group received visuoauditory feedback immediately after each trial informing them about the accuracy of their passes. Results: The results show that only players of the AF group significantly improved passing accuracy, reactiveness, and global passing performance (+22%), whereas the NF group only improved passing accuracy. None of these parameters was improved in the CON group. The objectively measured changes in passing performance were compared with the more subjectively judged passing performance provided by coaches and players. Coaches` judgments were more reliable than players` judgments and exhibited a training group effect comparable to the ones objectively measured by COGNIFOOT. Conclusions: This study provides evidence that the training of cognitive motor performance in soccer players highly benefits from the use of augmented feedback.